Effects of Si, Sn, Sr, Zn, and Zr on microstructure and properties of magnesium alloys for biomedical applications: a review - Rajadurai Murugesan; Siva Marimuthu; Manikandan Natarajan; Srikanth Holalu Venkataramana; Praveena Bindiganavile Anand; Muhammad Imam Ammarullah (Philosophical Magazine Letters, 2025)
This review article critically examines the influence of alloying elements, namely silicon (Si), tin (Sn), strontium (Sr), zinc (Zn), and zirconium (Zr), on the microstructures, mechanical properties, and corrosion resistance of magnesium alloys, with the primary focus being on biomedical applications. Magnesium alloys have garnered significant attention owing to their lightweight nature and potential for enhancing product performance. This review systematically explores how these alloying elements impact mechanical properties, microstructural configurations, and corrosion resistance, shedding light on the intricate mechanisms governing these changes. Emphasis is placed on their role in improving tensile strength, hardness, and ductility while balancing corrosion resistance to meet industrial demands. Additionally, considering the growing interest in magnesium alloys for biomedical applications, this review briefly highlights their potential for biodegradable implants, where tailored alloy compositions can optimize biocompatibility and degradation rates. A comprehensive synthesis of existing research findings offers valuable insights for researchers, engineers, and practitioners in optimizing magnesium alloys for biomedical applications.